Prevalence and risk factor assessment of Tropheryma whipplei in a rural community in Gabon: a community‐based cross‐sectional study. (November 2014) - Ramharter, M.; Harrison, N.; Bühler, T.; Herold, B.; Lagler, H.; Lötsch, F.; Mombo‐Ngoma, G.; Müller, C.; Adegnika, A. A.; Kremsner, P. G.; Makristathis, A.; Raoult, D.
Abstract Tropheryma whipplei is the causative agent of Whipple's disease and has been detected in stools of asymptomatic carriers. Colonization has been associated with precarious hygienic conditions. There is a lack of knowledge about the epidemiology and transmission characteristics on a population level, so the aim of this study was to determine the overall and age‐specific prevalence of T. whipplei and to identify risk factors for colonization. This molecular epidemiological survey was designed as a cross‐sectional study in a rural community in Central African Gabon and inhabitants of the entire community were invited to participate. Overall prevalence assessed by real‐time PCR and sequencing was 19.6% (95% CI 16–23.2%, n = 91) in 465 stool samples provided by the study participants. Younger age groups showed a significantly higher prevalence of T. whipplei colonization ranging from 40.0% (95% CI 27.8–52.2) among the 0–4 year olds to 36.4% (95% CI 26.1–46.6) among children aged 5–10 years. Prevalence decreased in older age groups (p <0.001) from 12.6% (95% CI 5.8–19.4%; 11–20 years) to 9.7% (95% CI 5.7–13.6) among those older than 20. Risk factor analysis revealed young age, male sex, and number of people sharing a bed as factors associated with an increased risk for T. whipplei carriage. These results demonstrate that T. whipplei carriage is highly prevalent in this part of Africa. The high prevalence in early life and the analysis of risk factors suggest that transmission may peak during childhood facilitated through close person‐to‐person contacts.